Are Nation and Exile a Woman? - the case of David Albahari’s novel Bait - Milan Miljković (Slovo, 2016)
Download this article from UCL Discovery. This article analyses contemporary Serbian writer David Albahari's novel Bait. Building a fragmented, sometimes self-involved fictional autobiography, the narrator constantly incorporates a variety of gender or femininity/masculinity issues, indirectly suggesting that the engendering of national identity and the exile experience could help articulate alternative types of discourses, non-patriarchal and non-ideological, those that would strongly and effectively oppose the grand narratives of History.